Synthesis and Characterization of Mixed Ligand Complexes of Nickel(II) with Histidine and Hippuric Acid - KUMAR, G. (Asian Journal of Chemistry, 2024)
Mixed ligand complexes of nickel(II) with the composition Na2[Ni(C6H5CONHCH2COO)(C6H8N3O2)·H2O]·7H2O and Na2[Ni(C6H5- CONHCH2COO)(C6H8N3O2).H2O]·H2O formed with histidine and hippuric acid have been synthesized. The mode of coordination and their structures have been examined by elemental analysis, infrared, electronic spectra and magnetic measurements. Histidine has shown a tridentate behaviour with the coordination occurring through the carboxylate oxygen atom and two nitrogen atoms of the imidazole and -NH2 groups. Hippuric acid has been found to act as a bidentate ligand coordinating through carboxylate oxygen atom and the nitrogen of the amido group.